Formation and dissipation dynamics of the Asian tropopause aerosol layer - Qianshan He; Jianzhong Ma; Xiangdong Zheng; Yanyu Wang; Yuhang Wang; Haizhen Mu; Tiantao Cheng; Ruilian He; Guan Huang; Dongwei Liu; Jos Lelieveld (Environmental Research Letters, 2020)
The Asian tropopause aerosol layer (ATAL) is characterized by enhanced aerosol concentrations in the Asian summer monsoon anticyclone in the upper troposphere and lower stratosphere at 13–18 km altitude. A growing body of evidence suggests that the aerosol enhancement is closely connected with deep convection during the monsoon. However, the origin of the aerosols is under debate, and the key factors that determine the ATAL variability remain poorly understood. We investigated the formation and dissipation mechanisms of the ATAL and the inter-annual variation from a dynamical viewpoint using satellite observations and meteorological reanalysis data from 2012 to 2018. We identified the northern Bay of Bengal and adjacent land area, where air pollution from the Indian subcontinent converges, as the major convection source area of aerosols to the ATAL. The spatial extent of the ATAL, represented by the mean attenuated scattering ratio from satellite measurements, appears to be related to a secondary circulation driven by the stratospheric quasi-biennial oscillation. The aerosols are not homogeneously distributed within the ATAL, and descending motion in the western part is found to play an important role in dissipation of the layer. These findings elucidate the ATAL dynamics and associated regional and global air pollution transports.